Ethical Readiness Gap dalam Pemanfaatan Chatgpt di Pendidikan Menengah: Studi Persepsi, Sikap, dan Kesiapan Institusi - Roni Herdianto; Zahira Tsuraya Asyrani; Anis Nurhayati; Dzikra Syahidin (Kayon Media, 2025)
Abstract:The widespread use of ChatGPT among high school students raises ethical challenges largely unaddressed by schools. This study identifies students' perceptions, ethical attitudes, and institutional readiness, and formulates the Ethical Readiness Gap (ERG) construct. Using a quantitative descriptive survey of 150 eleventh-grade students at SMA Negeri 1 Kota Blitar, a four-point Likert questionnaire measured perception (10 items), ethical attitude (11 items), and school readiness (6 items), analysed descriptively. Perception was very positive (M = 3.26), ethical attitude positive (M = 3.24), and school readiness positive but lowest (M = 2.87). Three interrelated ERG dimensions emerged: a cognitive–conative gap between principle endorsement (94.7%) and practised transparency (40.0%); an institutional–individual gap, with the school lagging behind students; and a normative–regulative gap, marked by absent formal policy despite strong demand (80%) for guidance, socialisation, and teacher capacity building. ERG is proposed as a diagnostic framework for secondary schools facing generative AI disruption. Abstrak:Pemanfaatan ChatGPT di kalangan pelajar SMA menimbulkan tantangan etis yang belum direspons institusi pendidikan. Penelitian ini mengidentifikasi persepsi, sikap etis, dan kesiapan institusional, serta merumuskan konstruk Ethical Readiness Gap (ERG). Survei kuantitatif deskriptif terhadap 150 siswa kelas XI SMA Negeri 1 Kota Blitar menggunakan kuesioner Likert empat poin: persepsi (10 butir), sikap etis (11 butir), kesiapan sekolah (6 butir); dianalisis deskriptif. Persepsi sangat positif (M = 3,26), sikap etis positif (M = 3,24), kesiapan sekolah positif namun terendah (M = 2,87). Tiga dimensi ERG teridentifikasi: gap kognitif-konatif antara pengakuan prinsip etis (94,7%) dan kesediaan praktik transparansi (40,0%); gap institusional-individual, yakni kesiapan kelembagaan tertinggal dari siswa; serta gap normatif-regulatif, yakni absennya kebijakan formal meski 80% siswa mengharapkan panduan, sosialisasi, dan peningkatan kapasitas guru. ERG diusulkan sebagai kerangka diagnostik kesiapan etis sekolah menghadapi AI generatif, dengan rekomendasi pedoman tertulis, pelatihan literasi AI bagi guru, dan budaya transparansi akademik berbasis bukti